Additions to thalassinidean fauna (Crustacea: Decapoda) off Mauritania (NW Africa) with the description of a new genus and a new species - Matos-Pita, Susana S. De; Ramil, Fran (Zootaxa, 2015)
The Maurit surveys along the Mauritanian coast revealed the small collection of thalassinideans examined in this work. A total of four species were identified, of which Ezaxius ferachevali n. gen., n. sp. is described and figured here. Calocaris macandreae Bell, 1853 is the most abundant species, while the presence of Calocarides coronatus (Trybom, 1904) is confirmed on the West African coast. Trypaea oblonga n. comb. is proposed for Callianassa oblonga Le Loeuff & Intès, 1974 and it has been recaptured for the first time since its original description, with the addition of a female specimen. We also include remarks on the current status of thalassinidean systematics.